Crossing the Indian Ocean: a range extension for Goreopagurus poorei Lemaitre & McLaughlin, 2003 (Crustacea: Decapoda: Paguridae) - Landschoff, Jannes; Lemaitre, Rafael (Zootaxa, 2017)
Goreopagurus poorei Lemaitre & McLaughlin, 2003, a hermit crab of the family Paguridae previously known only from off eastern Tasmania in the Tasman Sea, has been discovered in the western Indian Ocean off the coast of South Africa, extending considerably the range of this species by 10,100 km to the west. While this finding represents a large range extension, similar wide ranges are frequent and well known in other deep-water decapods including paguroids. Colour information and minor morphological variations are presented to complement the morphological information provided in the original description. Genetic sequence data is also provided for future use in phylogenetic and biogeographic studies.